Targeting inflammation and oxidative stress in atrial fibrillation: role of 3-hydroxy-3-methylglutaryl-coenzyme a reductase inhibition with statins. - Pinho-Gomes, A; Reilly, S; Brandes, R; Casadei, B (2014)
SIGNIFICANCE: Atrial fibrillation (AF) is a burgeoning health-care problem, and the currently available therapeutic armamentarium is barely efficient. Experimental and clinical evidence implicates inflammation and myocardial oxidative stress in the pathogenesis of AF. RECENT ADVANCES: Local and systemic inflammation has been found to both precede and follow the new onset of AF, and NOX2-dependent generation of reactive oxygen species in human right atrial samples has been independently associated with the occurrence of AF in the postoperative period in patients undergoing cardiac surgery. Anti-inflammatory and antioxidant agents can prevent atrial electrical remodeling in animal models of atrial tachypacing and the new onset of AF after cardiac surgery, suggesting a causal relationship between inflammation/oxidative stress and the atrial substrate that supports AF. CRITICAL ISSUES: Statin therapy, by redressing the myocardial nitroso-redox balance and reducing inflammation, has emerged as a potentially effective strategy for the prevention of AF. Evidence indicates that statins prevent AF-induced electrical remodeling in animal models of atrial tachypacing and may reduce the new onset of AF after cardiac surgery. However, whether statins have antiarrhythmic properties in humans has yet to be conclusively demonstrated, as data from randomized controlled trials specifically addressing the relevance of statin therapy for the primary and secondary prevention of AF remain scanty. FUTURE DIRECTIONS: A better understanding of the mechanisms underpinning the putative antiarrhythmic effects of statins may afford tailoring AF treatment to specific clinical settings and patient's subgroups. Large-scale randomized clinical trials are needed to support the indication of statin therapy solely on the basis of AF prevention.